Cysteine-Specific Cu(2+) Chelating Tags Used as Paramagnetic Probes in Double Electron Electron Resonance - Cunningham, Timothy F. (J Phys Chem B, 2015)
[Image: see text] Double electron electron resonance (DEER) is an attractive technique that is utilized for gaining insight into protein structure and dynamics via nanometer-scale distance measurements. The most commonly used paramagnetic tag in these measurements is a nitroxide spin label, R1. Here, we present the application of two types of high-affinity Cu(2+) chelating tags, based on the EDTA and cyclen metal-binding motifs as alternative X-band DEER probes, using the B1 immunoglobulin-binding domain of protein G (GB1) as a model system. Both types of tags have been incorporated into a variety of protein secondary structure environments and exhibit high spectral sensitivity. In particular, the cyclen-based tag displays distance distributions with comparable distribution widths and most probable distances within 1–3 Å when compared to homologous R1 distributions. The results display the viability of the cyclen tag as an alternative to the R1 side chain for X-band DEER distance measurements in proteins.